OUTCOME BASED LEARNING: THE EFFECT OF EXPERIENTIAL LEARNING ACTIVITY ON DEEP CONCEPTUAL UNDERSTANDING - Thote, Prashant; S, Gowri (International Journal of Research -GRANTHAALAYAH, 2021)
The aim of the present study is to investigate the effect of experiential learning activity in deep conceptual understanding of science in comparison with conventional teaching model. In the present experiment quasi experimental and post-test research design is implemented. Totally 80 students participate in the study: 40 girls and 40 boys. The sample is categorized into two: study and the control group. Each group consists of 40 students: 20 boys and 20 girls. The study group is taught “Gases Law” by using experiential learning activities and the control is taught by using the conventional method. Data is collected by using a questionnaire and it consists of 20 multiple choice questions. The collected data is analyzed by using descriptive statistics. The examination of the data illustrates that there is no noteworthy difference in the mean score between the study group and the control group. Independent ‘t-test’ is applied to compare the student’s achievement in post-test. The mean score of the study group, who are exposed to the experiential learning activities, in Science Achievement post-test is 17.35. It is higher than that of (t=6.65; p>0.01) the learners in the control group. The mean of the control group is 14.45. Therefore, it is concluded that the experiential learning activities as a teaching model enhances the deep conceptual understanding of science.